Penerapan Model Pembelajaran Make A Match Dalam Meningkatkan Hasil Belajar IPA - Nuraidawati Nuraidawati (JURNAL GLOBAL EDUKASI, 2022)
Abstract: In order to increase student participation and activeness in class, the teacher applies the make a match learning model. The make a match learning model or looking for a partner is an alternative that can be applied to students. This research was conducted to apply the Make a Match learning model to science lessons on the subject matter of the Solar System to improve student learning outcomes in class VII SMP Negeri 1 Tinggi Raja Kab. Sharpen. Based on the discussion, it can be concluded that the results of the learning process before the research Application of the Make a Match Method reached an average value of 56.91 after being motivated to do research through cycle I and cycle II of reflection and recommendations the average value reached 88.72 meaning there was an increase of 28.26 . The learning outcomes in cycle I achieved mastery of classical learning by 71.84% after cycles I and cycle II, reflections and recommendations for classical learning mastery reached 85.17%, meaning there was an increase of 13.33%.Keywords: make a match; solar system  Abstak: Guna meningkatkan partisipasi dan keaktifan siswa dalam kelas, guru menerapkan model pembelajaran make a match. Model pembelajaran make a match atau mencari pasangan merupakan salah satu alternatif yang dapat diterapkan kepada siswa. Penelitian ini dilakukan untuk menerapkan model pembelajaran Make a Match pada pelajaran IPA materi pokok Tata Surya untuk meningkatkan hasil belajar siswa kelas VII SMP Negeri 1 Tinggi Raja Kab. Asahan. Berdasarkan pembahasan dapat disimpulkan hasil proses belajar sebelum penelitian Penerapan Metode Make a Match mencapai nilai rata-rata 56,91 setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 88,72 berarti ada peningkatan sebesar 28,26. Hasil belajar pada siklus I mencapai ketuntasan belajar klasikal sebesar 71,84% setelah siklus I dan siklus II, refleksi dan rekomendasi ketuntasan belajar klasikal mencapai 85,17% berarti ada peningkatan sebesar 13,33%.Kata kunci: make a match; tata surya